Modelling New Zealand Consumption Expenditure over the 1990s - Khoon Lek Goh; Richard Downing (New Zealand Government, The Treasury, 2002)
This paper presents two models of consumption for the primary purpose of forecasting consumption expenditure growth in New Zealand. The models, which are consistent with a range of consumption functions including the life-cycle and permanent income hypothesis, are error correction models with the long-run equations estimated using both the conventional ordinary least squares procedure as well as the Stock and Watson procedure of leads and lags. Unlike earlier New Zealand studies, actual data on household net wealth, rather than proxies or derived series were used. This allowed the wealth variable to modelled in disaggregated form. Mortgage equity withdrawal by households and funds brought into the economy by immigrants are two novel variables included in the consumption models. Migrant transfers were found to have an influence on short-run consumption growth, but not mortgage equity withdrawal although the latter did contribute to a higher overall model fit. Net non-financial wealth was found to have short-run influence on consumption but not in the long-run.
Keywords: D12; D91; E21; E27; 330; Forecasting; consumption functions; wealth; migrant transfers; mortgage equity withdrawal